ANALYSIS OF ENTREPRENEURSHIP ORIENTATION, ADAPTABILITY OF BUSINESS ENVIRONMENT, AND INTERNAL RESOURCES COMPANY ON COMPETITIVE ADVANTAGES TO IMPROVE COMPANY PERFORMANCE (Study at Micro Small and Medium Enterprises Embroidered Kudus District) - Ayuningtyas, Aulia Ardhian; Miyasto, Miyasto; Sugiarto, Yohanes (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2018)
Economic development in Indonesia MSMEs has an important role because the majority of Indonesia's population lives from MSME activities both in the traditional and modern sector. MSME in Central Java is also quite good. However, MSMEs in Central Java also experienced an increase in competitiveness, especially with similar businesses. Therefore, entrepreneurs are required to be able to innovate and dare to explore the resources it has for its business can continue to grow and survive amid the competition. In this study, the authors explain the condition of competitiveness of SMEs in the Kudus Regency is the business of embroidery which from year to year always decreased. Based on the result of the theoretical study directing this study developed a model with five research variables covering entrepreneurial orientation, business environment adaptability, internal resources of company, competitive advantage, and company performance. The results of the analysis show that the entrepreneurship orientation does not positively affect the competitive advantage. The adaptability of the business environment positively affects the competitive advantage. Internal resources of the company positively influence the competitive advantage. Entrepreneurship orientation positively affects the company's performance. Internal resources of the company positively affect the company's performance. Competitive advantage positively affects the company's performance.